Gout‐associated uric acid crystals induce tophi ulcerations and impair wound healing in a novel gouty ulcer model. Issue 1 (19th October 2021) - Bao, Wu; Xue, Yi; Cheng, Xialin; Wang, Peng; Yin, Bin; Su, Yingjun; Jia, Chiyu
Abstract: This study aimed to establish a novel gouty ulcer rat model induced by monosodium urate (MSU) deposition and preliminarily explored how MSU crystals affected wound healing. MSU crystals were subcutaneously injected into the back of rats to simulate tophi formation and ulceration. Ultrasound was used to detect the formation of gouty tophi. MSU crystal deposition and histopathological changes were analysed by haematoxylin–eosin staining. After the skin over the tophi became broken in the model group, a full‐thickness tissue defect of the same area was made on the backs of the phosphate buffered saline (PBS) controls. On Days 3, 7, and 14 after wounding, the infiltration of neutrophils and macrophages and the expression of inflammatory markers, including interleukin‐1β (IL‐1β), tumour necrosis factor‐α (TNF‐α), and Nod‐like receptor protein 3 (NLRP3), were examined by immunohistochemical staining and Western blotting, respectively. After the first subcutaneous injection in rats, local tissues showed redness and swelling, indicating inflammation on approximately Day 14. Tophi‐like manifestations appeared on approximately Day 18. Tophi appeared heterogeneously hyperechoic by ultrasound. Swelling and redness in injured tissue areas increased on approximately Day 22, skin tissue necrosis was seen in a small area on approximately Day 26, and skin necrosis was enlarged and the tophi were ulcerated on approximately Day 32, accompanied by yellowish‐white, chalky secretions. Haematoxylin and eosin staining showed dermal deposition of needle‐like crystals with surrounding granulomatous inflammation. On Days 3, 7, and 14 after wounding, immunohistochemical staining showed the infiltration of neutrophils and macrophages, and the expression of inflammation‐related proteins (IL‐1β, TNF‐α, and NLRP3) were upregulated in gouty ulcers compared with those of PBS controls. The gouty ulcers were not completely healed by Day 14 compared with those in the PBS controls. In this study, a novel gouty ulcer rat model was constructed, which also revealed the existence of persistent chronic inflammation.